2009
DOI: 10.1126/science.1175455
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of Antigen-Specific CD8 + T Cells in Response to Infection Is Markedly Efficient

Abstract: The magnitude of antigen-specific CD8+ T cell responses is not fixed but correlates with the severity of infection. Although by definition T cell response size is the product of both the capacity to recruit naïve T cells (clonal selection) and their subsequent proliferation (clonal expansion), it remains undefined how these two factors regulate antigen-specific T cell responses. We determined the relative contribution of recruitment and expansion by labeling naïve T cells with unique genetic tags and transferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
130
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(148 citation statements)
references
References 18 publications
15
130
1
2
Order By: Relevance
“…The presence of those same TCRb clonotypes in the naive pool would then derive from thymic replenishment of the naive repertoire with identical TCR sequences. Indeed, recent studies in mice showed that, although governed by affinity for peptide-MHC (11,41), recruitment of Ag-specific CD8 + T cells from the naive pool is markedly efficient (9). This scenario is supported by our observations that TCRb clonotypes common to the memory and naive pools tended to have larger sizes in both pools and are more efficiently generated by convergent recombination.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The presence of those same TCRb clonotypes in the naive pool would then derive from thymic replenishment of the naive repertoire with identical TCR sequences. Indeed, recent studies in mice showed that, although governed by affinity for peptide-MHC (11,41), recruitment of Ag-specific CD8 + T cells from the naive pool is markedly efficient (9). This scenario is supported by our observations that TCRb clonotypes common to the memory and naive pools tended to have larger sizes in both pools and are more efficiently generated by convergent recombination.…”
Section: Discussionsupporting
confidence: 77%
“…Yet, this approach should be considered in light of the dynamic relationship between these two populations, which involves continuous thymic output of new naive T cells, homeostatic maintenance of the peripheral repertoire, and recruitment of naive T cells to the memory pool through episodic and persistent antigenic stimulation (7,8). Recruitment from the naive T cell pool seems to be highly efficient (9), such that even CD8 + T cell clonotypes with very low avidity for cognate Ag (10,11) are mobilized from the naive repertoire. Therefore, one might expect that the clonotypic landscape of the memory T cell repertoire after initial recruitment should reflect the hierarchical distribution of available clonotypes within the naive T cell repertoire.…”
mentioning
confidence: 99%
“…The focus to date has, however, been on the more prominent pMHCI-specific CTL sets, with the implication being that all the naive CTLps are recruited into the immune response. This is also the conclusion of a recent study that tracked recruitment of genetically tagged TCR Tg T cells after transfer (17). But is that indeed the case in a polyclonal T cell response to viral infection, and is CTLp prevalence the overarching determinant of CTL response magnitude?…”
Section: Introductionmentioning
confidence: 89%
“…Efficient recruitment into and survival through an immune response requires that responding T cells achieve a necessary level of "fitness" by crossing various signaling thresholds (3,5). The primary measure of such molecular "fitness" is considered to be the strength of TCR/ pMHCI binding (6), which determines the differential selection of naive precursors into an immune response (7)(8)(9), the spectrum of subsequent clonal expansion and extent of differentiation to effector/memory status (6,9). What constitutes optimal, or even sufficient, TCR/pMHCI affinity/avidity is, however, a matter of debate, with different conclusions being reached from a variety of in vivo and in vitro approaches using altered peptide ligands (APLs) (4,(9)(10)(11)(12)(13)(14).…”
Section: Irus-specific Cd8mentioning
confidence: 99%